2020
DOI: 10.3126/njz.v4i1.30672
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution patterns of ants along elevational gradients

Abstract: Ants are one of the most successful groups of organisms present in almost all terrestrial habitats on the Earth. The published papers on ants with various sampling techniques were reviewed focusing on species richness along the elevational gradients to explain distribution patterns of ants and their potential drivers in the world. Pitfall trapping, hand collection, Winkler extractor and bait traps were found common sampling techniques for ant studies. Based upon literature, five broad distributional patterns w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Interestingly, consideration of the elevational distribution of singletons and doubletons indicated that rare species contribute to species richness at both low and higher elevation in the Pieniny Mts. Our results for clinocerines corresponds with data received for many other insect groups studied in different mountain areas of the world [ 13 , 18 , 19 , 20 , 21 , 23 , 24 ], even if a great percentage of these studies were made in much higher mountain massifs than the Pieniny Mts. In contrast to our study, a different trend was found for some other aquatic and terrestrial invertebrate groups studied in Polish mountain massifs including Mount Babia, Tatra Mts., and Bieszczady Mts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, consideration of the elevational distribution of singletons and doubletons indicated that rare species contribute to species richness at both low and higher elevation in the Pieniny Mts. Our results for clinocerines corresponds with data received for many other insect groups studied in different mountain areas of the world [ 13 , 18 , 19 , 20 , 21 , 23 , 24 ], even if a great percentage of these studies were made in much higher mountain massifs than the Pieniny Mts. In contrast to our study, a different trend was found for some other aquatic and terrestrial invertebrate groups studied in Polish mountain massifs including Mount Babia, Tatra Mts., and Bieszczady Mts.…”
Section: Discussionsupporting
confidence: 90%
“…Among them, eleven species are known as rare including four currently recognized as endemics to this mountain massif [61,63,89]. Aquatic empidids were decidedly dominated by the subfamily Clinocerinae (almost 98% total fauna) which was represented by 24 . In total, almost 60% of all aquatic empidids collected in the study were caught in the Dunajec, the major river in the Pieniny Mts., with Wiedemannia bistigma as the most abundant species recorded at all sampling sites along this river (19,038 individuals or 46.3% of clinocerines).…”
Section: Species Composition Species Richness and Diversity Along Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in the distribution of the forest ants of Nepal with elevation is in line with other studies. The highest number of ant genera in our study was recorded below 1000 m asl, and there was a decreasing pattern with the increase in elevation (Figure 4) as reported by Subedi and Budha [64] when they extrapolated available elevation-related records of ants of Nepal from 200 m to 4550 m. A decreasing pattern is one of the most common patterns of ant species richness [64,65]. A number of studies from different parts of the world also reported a decreasing pattern of species richness with elevation, such as those from Mount Kinabalu [66], the Mediterranean and the oro-Mediterranean parts of Montenegro [67], rainforest in subtropical Queensland [68], wet forest on Costa Rica's Atlantic slope [69], Imbak Canyon [70], Hengduan Mountains [71], and eastern Himalaya [15].…”
Section: Distribution Of Ants In Nepalsupporting
confidence: 83%
“…Many regions of Nepal are clearly under sampled, such that future exploration should reveal additional species. The insufficient collections and limited published information present challenges to determining and evaluating distribution patterns of Nepalese ants ( Subedi and Budha 2020 ). However, the checklist presented here provides a waypoint for further studies of diversity and distribution of Nepalese ants.…”
Section: Resultsmentioning
confidence: 99%